2007
DOI: 10.1681/asn.2006101124
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species in the Presence of High Glucose Alter Ureteric Bud Morphogenesis

Abstract: Renal malformations are a major cause of childhood renal failure. During the development of the kidney, ureteric bud (UB) branching morphogenesis is critical for normal nephrogenesis. These studies investigated whether renal UB branching morphogenesis is altered by a high ambient glucose environment and studied underlying mechanism(s). Kidney explants that were isolated from different periods of gestation (embryonic days 12 to 18) from Hoxb7-green fluorescence protein mice were cultured for 24 h in either norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 43 publications
(59 reference statements)
4
50
0
Order By: Relevance
“…Renal injury has been reported previously in our Dia-ND mice (9)(10)(11)(12)(13). In this work, we found that HFD augmented TGFβ1 and collagen IV gene expression, increased renal lipid accumulation, as well as heightened oxidative stress in both glomerular and tubular compartments in the kidneys of Dia-HF mice, resulting in significant glomerulosclerosis, tubular fibrosis, and apoptosis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Renal injury has been reported previously in our Dia-ND mice (9)(10)(11)(12)(13). In this work, we found that HFD augmented TGFβ1 and collagen IV gene expression, increased renal lipid accumulation, as well as heightened oxidative stress in both glomerular and tubular compartments in the kidneys of Dia-HF mice, resulting in significant glomerulosclerosis, tubular fibrosis, and apoptosis.…”
Section: Discussionsupporting
confidence: 79%
“…Such offspring showed impaired nephrogenesis resulting in nascent nephron deficiency in neonate and manifested hypertension, glucose intolerance, and kidney injury in adulthood. The possible mechanisms involved in those phenomena include reactive oxygen species (ROS) elevation and activation of the nuclear factor-kappa B (NFkB), TGFβ1, and p53 pathways (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…The results from those four studies mentioned above might draw a conclusion that the increased expression of PAX2 took part in the progression of RIF. Furthermore, ROS could induce the PAX2 expression, 49,50 and overexpression of PAX2 was found in the renal tissue affected by RIF. 30 PAX2 was associated with the development of RIF.…”
Section: Mrna Expression Of Pax2mentioning
confidence: 98%
“…Autosomal recessive mutations in the coenzyme Q(10) protein leads to glomerular damage via decreased activity of complex II ϩ III in abnormal mitochondrions in podocytes (54). Blockade of mitochondrial complex I leads to lack of ureteric bud-branching morphogenesis in response to high glucose (383). Hyperglycemia induces mitochondrial electron-transport chain enzymes in cultured human mesangial cells to increase ROS production, leading to NF-B activation and COX-2 protein expression (162).…”
Section: Role Of Renal Oxidative Stress In Hypertension 2053mentioning
confidence: 99%